Eschershia coli integrons and cfr, procfr genes identified from samples of autistic children's stools - Khwam Reissan Hussein,; NimahJulud Al- Temimy,; Qasim Hassan Widaa,; Marwa Hassan Nasser, (University of Thi-Qar Journal of Science, 2023)
Escherichia coli is a Gram-negative Bacilli belonging to the Enterobacteriaceae family. It has a rod-shaped coliform . A number of neuropsychiatric conditions, likeanxiety, schizophrenia, autism, bipolar disorder, and depressive disorder, Have been reported to be associated with the microbiome. Autism spectrum disorder (ASD), is a neurodevelopmental disturbance. A sample of fifteen E.coli bacteria were isolated E. coliisolates From ASD children's stools.ASD children. The isolates were identified by phenotypic identification using API 20 E. The molecular analysis was processed for Integron I,II,I, cfr, procfr genes.These resultsshowed Integron II less prevalence Than in IntegronIand III. I,III while pro-cfr, more prevalence than cfrgene.Multidrug-resistant in E. coli has widespread.